Antecedents of export marketing performance: The moderating role of environmental knowledge and government intervention - R Rohwiyati; Tulus Haryono; Ahmad Ikhwan Setiawan; Lilik Wahyudi; S Sulistya (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2025)
This research aims to investigate effect green market orientation (GMO) and green intellectual capital (GIC) on green innovation (GI) and its impact on export marketing performance (EMP) and testing moderating role effect GI on EMP. Research Methods: samples 116 Micro, Small, and Medium Enterprises (msmes) Central Java Indonesia, Partial Least Squares Structural Equation Modeling (PLS-SEM) used to data analyzing. Findings: GMO and GIC Impact on GI: Both green market orientation and green intellectual capital have a significant positive effect on green innovation. Impact on EMP: Green market orientation and green innovation significantly influence export marketing performance. Green intellectual capital does not have a significant direct effect on export marketing performance. Moderating Role of Environmental Knowledge and Government Intervention: Environmental knowledge and government intervention positively moderate the relationship between green innovation and export marketing performance, strengthening the impact of green innovation on EMP. Values: Insight for msmes: The study provides valuable insights for MSME coffee exporters in Central Java, emphasizing the importance of focusing on enhancing environmental knowledge and leveraging government intervention to achieve better marketing success in the global market.